Pengaruh Program Relawan Pajak dan Pendampingan oleh Relawan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Inayah Inayah; Afifudin Afifudin; Umi Nandiroh (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Tax Volunteer Programs and Assistance by Tax Volunteers can motivate someone to pay taxes as a voluntary contribution to the state which can affect taxpayer compliance. This study aims to determine the effect of the Tax Volunteer Program and Assistance by Tax Volunteers on Individual Taxpayer Compliance. This research is a quantitative research using primary data. The sampling technique in this study was carried out by purposive sampling. The results of this study indicate: 1) Simultaneously the variables of the tax volunteer program and assistance by tax volunteers have a significant effect on individual taxpayer compliance, 2) The results of the hypothesis test show that the tax volunteer program variable has a significant positive effect on individual taxpayer compliance, 3) The results of the hypothesis test show that the assistance variable by tax volunteers has a significant positive effect on individual taxpayer compliance.Keywords: Tax volunteer program, tax volunteer assistance and taxpayer compliance